Central Management of Research Misconduct in the USA and Canada - Shuster, Jonathan (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
This paper proposes major changes in how research misconduct cases should be managed in the USA and Canada. Specifically, I advocate for centralized oversight that completely removes research institutions from this role in order to: mitigate institutional conflicts of interest, standardize definitions of research misconduct, better preserve confidentiality of complainants (those alleging misconduct), ensure that cases are not screened for rejection, mobilize a review panel of experts who are free of conflicts of interest, avoid inappropriate collective punishment of institutions, and ultimately save resources as compared to current decentralized systems. Two cases which this author, as complainant, alleged research misconduct (in the USA and Canada) demonstrate clearly how far institutional Research Integrity Officers can go to prevent an impartial expert review. Given that our institutions and scientific community rightly have zero tolerance for research misconduct, the current decentralized practice should be a grave concern to those who hope to trust in proper oversight. A discussion follows, including comments on new directives for 2025 from the US Office of Research Integrity and the implications of high-profile cases. I conclude with details as to how cases might be brought to justice under the proposed centralized process.